Local fractional variational iteration and decomposition methods for wave equation on cantor sets within local fractional operators - Baleanu, Dumitru (2014)
We perform a comparison between the fractional iteration and decomposition methods applied to the wave equation on Cantor set. The operators are taken in the local sense. The results illustrate the significant features of the two methods which are both very effective and straightforward for solving the differential equations with local fractional derivative.